Beta‐lactamase‐producing Escherichia coli in Bangladesh: Their phenotypic and molecular characteristics (Dhaka University Journal of Biological Sciences, 2019)
The emergence and rapid dissemination of beta-lactamase-producing E. coli is now a worldwide problem. A total of 45 E. coli obtained from clinical specimens from a medical service centre in Dhaka were selected for this study. Test E. coli exhibited variable resistance to 3rd (71.7 - 97.8%, n = 48) and 4th (78%, n = 48) generation beta-lactam antibiotics, with 72% sensitivity to Carbapenem. Analysis of co-resistance indicated that 33.3% of E. coli (n = 48) were co-resistant to beta-lactams and ciprofloxacin. ESBL producers were predominant comprising of 84.7% E. coli. Among them, 22.7% contained blaTEM, 24.2% contained blaCTX-M, 4.3% contained blaSHV and 9.1% contained blaOXA-1 genes. A total of 25.75% isolates were metallo beta-lactamase producers. Of these, 1.5% of E. coli strains contained New Delhi metallo beta-lactamase gene and 6% contained AmpC gene. Multiple beta-lactamase genes were detected in some test isolates; 6.7% isolates contained 4, 20% contained 3 and 73.3% contained 2 beta lactamase genes. Fifty per cent of the E. coli contained plasmids of variable sizes. In addition, a total of 39% of the E. coli contained Class 1 integron. The increasing trend in beta-lactam resistance is of public health concern as it limits treatment regime and indicates to the need of continuous monitoring of resistance pattern.Dhaka Univ. J. Biol. Sci. 28(1): 71-81, 2019 (January)